2021
DOI: 10.1007/s11665-021-06101-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Microstructural Evolution and Mechanical Properties of Laser Metal Deposited 316L Stainless Steel

Abstract: Laser metal deposition (LMD) method is considered as a promising additive manufacturing technique owing to its advanced features. This includes printing complex shaped structures via three-dimensional computer-aided-designs, laser cladding and rapid prototyping. In the present study, detailed microstructure-property correlation is pursued for a block of 316L stainless steel alloy, manufactured by LMD. Presence of fully austenitic phase with corresponding residual stresses in the as-built structure is observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Our implant surfaces possess a roughness that falls within the micrometer range. Consequently, these implants might facilitate in vitro cell adhesion, viability, and osteogenic differentiation, similar to the observations made with titanium having increased surface roughness [24]. Prior to cells sticking to biomaterial surfaces, proteins get absorbed from body fluids, controlling subsequent cell adhesion and behavior.…”
Section: Materials Propertiesmentioning
confidence: 53%
See 1 more Smart Citation
“…Our implant surfaces possess a roughness that falls within the micrometer range. Consequently, these implants might facilitate in vitro cell adhesion, viability, and osteogenic differentiation, similar to the observations made with titanium having increased surface roughness [24]. Prior to cells sticking to biomaterial surfaces, proteins get absorbed from body fluids, controlling subsequent cell adhesion and behavior.…”
Section: Materials Propertiesmentioning
confidence: 53%
“…His XRD diffraction peak of Ti6Al4V was detected at 40°, indicating the presence of a peak corresponding to the structure of Ti6Al4V. Furthermore, the peak at 53° matched the structure of ST316L [23,24]. The XRD diffraction peak of polyamide 12 was detected at 21°, indicating the presence of a peak corresponding to the structure of polyamide 12.…”
Section: Phase Identification With Xrd Micrographmentioning
confidence: 91%
“…Ti6Al4V XRD diffraction peaks were detected at 40°, which indicates Ti6Al4V has a structure consistent with the peaks. Further, the peaks at 53° correspond to the structure of ST316L [23,24].…”
Section: Phase Identification With Xrd Micrographmentioning
confidence: 97%
“…layer thickness, material and powder size). Empirical studies have shown that the microstructure evolution and mechanical properties of LPBF-produced metals are strongly correlated to the printing process parameters (Nath et al , 2021; Kotadia, 2021; Yadroitsev et al , 2007; Kruth et al , 2004). Therefore, such correlations can be valuable input to models that evaluate tradeoffs between cost and component quality, via considering how process parameters influence both build rate and desired properties and/or the formation of defects during AM.…”
Section: Introductionmentioning
confidence: 99%